Detection of chronic lung allograft dysfunction using ventilation‐weighted Fourier decomposition MRI. Issue 8 (26th May 2018) - Voskrebenzev, A.; Greer, M.; Gutberlet, M.; Schönfeld, C.; Renne, J.; Hinrichs, J.; Kaireit, T.; Welte, T.; Wacker, F.; Gottlieb, J.; Vogel‐Claussen, J.
Abstract : Chronic lung allograft dysfunction (CLAD) remains the leading cause of morbidity and mortality after lung transplantation. Diagnosis requires spirometric change, which becomes increasingly difficult with advancing CLAD. Fourier decomposition magnetic resonance imaging (FD‐MRI) permits acquisition of ventilated‐weighted images during free‐breathing. This study evaluates FD‐MRI in detecting CLAD in selected patients after bilateral lung transplantation (DLTx). DLTx recipients demonstrating CLAD at various stages participated. Radiologists remained blinded to clinical status until completion of image analysis. Image acquisition used a 1.5‐T MR scanner using a spoiled gradient echo sequence. After FD processing and regional fractional ventilation (RFV) quantification, the volume defect percentage at 2 thresholds (VDP1, 2 ), median lung RFV and quartile coefficient of dispersion (QCD) were calculated. Sixty‐two patients participated. CLAD was present in 29/62 (47%) patients, of whom 17/62 (27%) had forced expiratory volume in 1 second ≤65% at image acquisition. VDP1 was higher among these participants compared to other groups ( P  < .001). Increased VDP1 was associated with subsequent graft loss, with values >2% showing reduced survival, independent of degree of graft dysfunction ( P  = .005). VDP2 discriminated between presence or absence of CLAD (area under the curve = 0.71; P  = .03). QCD increased significantly with advancing disease ( P  < .001). In conclusion, FD‐MRI‐derived parameters demonstrate potential in quantitative CLAD diagnosis and assessment after DLTx. Abstract : Quantitative assessment of lung allograft function during normal breathing using contrast‐free MRI scanning identifies parameters potentially useful in both diagnosing and characterizing the pathophysiology of chronic lung allograft dysfunction.